2019
DOI: 10.1038/s41558-019-0425-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid growth in greenhouse gas emissions from the adoption of industrial-scale aquaculture

Abstract: Fisheries capture has plateaued, creating ever-greater reliance on aquaculture to feed growing populations. Aquaculture volumes now exceed those of capture fisheries globally 1,2 , with China dominating production through major land-use change; more than half of Chinese freshwater aquaculture systems having been converted from paddy fields 1,3. However, the greenhouse gas (GHG) implications of this expansion have yet to be effectively quantified. Here we measure year-round methane (CH 4), nitrous oxide (N 2 O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 26 publications
1
94
1
Order By: Relevance
“…freshwater emissions are separate from wetlands. Not yet included are probably minor emissions from glacial systems (other than permafrost soils) [22], terrestrial aquaculture [23] and breakdown of plastics in the environment [24]. In the GCP TD budget, at least half of the emissions are anthropogenic:~34% (BU 26%) of total from agriculture,1 9% (BU 16%) from fossil fuels, plus contributions from biomass and biofuel burning.…”
Section: The Total Methane Budget: Reconciling Bottom-up and Top-downmentioning
confidence: 99%
“…freshwater emissions are separate from wetlands. Not yet included are probably minor emissions from glacial systems (other than permafrost soils) [22], terrestrial aquaculture [23] and breakdown of plastics in the environment [24]. In the GCP TD budget, at least half of the emissions are anthropogenic:~34% (BU 26%) of total from agriculture,1 9% (BU 16%) from fossil fuels, plus contributions from biomass and biofuel burning.…”
Section: The Total Methane Budget: Reconciling Bottom-up and Top-downmentioning
confidence: 99%
“…Furthermore, the accurate estimate of the regional and global CH 4 budgets remains challenging also because of the overlooked role of small ponds (Holgerson, ; Holgerson & Raymond, ). As an important part of the global small ponds, some recent studies have suggested that aquaculture ponds can be indispensable CH 4 emission sources (Chen et al, ; Hu et al, ; Wu et al, ; P. Yang et al, ; Yuan et al, ). Although some efforts have been made on characterizing CH 4 fluxes in aquaculture ponds, the number of field records of CH 4 emissions from aquaculture ponds remains very scarce as compared to those from other aquatic systems (e.g., lakes and reservoirs; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture production is dominated by China's fish and crab ponds. Yuan et al () found a tripling of the CH 4 emissions per hectare per year when operating a fishpond instead of a rice paddy field. This finding contradicts Liu et al (), which calculated EFs from aquaculture to be half as large as those from rice paddy fields.…”
Section: Bottom‐up Modelingmentioning
confidence: 99%